TECHNOLOGICAL PROPERTIES OF Memecylon lateriflorum WOOD: A TIMBER SPECIES FROM GHANA (Nativa, 2023)
A critical aspect of the Sustainable Forest Management scheme is promoting lesser-used timber species in substituting the over-exploited timber species of similar technical characteristics. The study's main objective was to evaluate the technological properties within the tree height of Memecylon lateriflorum (G. Don) Bremek. They were using small clear, defect-free, straight-grained wood samples. Using standardized procedures, the samples were harvested, prepared, and conditioned from the diameter at breast height (DBH), middle, and top portion of the trees. The results indicated that the density of M. lateriflorum was 840 kg/m3, which characterizes it as a high-density wood. The study again revealed a strong correlation (83-99 %) between the woods' densities and mechanical strength characteristics. Also, the overall average tangential and radial shrinkage from green to 12 % moisture content was 9.46% and 6.57%, respectively, whereas that of longitudinal was 0.65%. The mean strength values recorded in N/mm2 at 12% moisture content were: modulus of elasticity (19.724), modulus of rupture (143.00), compression (62.40), shear (20.50), and tensile parallel to grain (149.20). Janka hardness test recorded mean values of 15.70 and 14.30 kN in the radial and tangential directions. Thus, M. lateriflorum could be promoted as an efficient choice for construction and structural applications.Keywords: valorization of wood; physical-mechanical properties; wood quality. Propriedades tecnológicas da madeira de Memecylon lateriflorum: uma espécie madeireira de Gana RESUMO: Um aspecto crítico do Manejo Florestal Sustentável é a promoção de espécies madeireiras menos utilizadas em substituição às espécies madeireiras traidionais. O objetivo principal do estudo foi avaliar as propriedades tecnológicas na altura da árvore de Memecylon lateriflorum (G. Don) Bremek. usando pequenas amostras de madeira clear (grã reta e sem defeitos). As amostras foram colhidas, preparadas e acondicionadas a partir do diâmetro à altura do peito (DAP), porção média e superior das árvores, utilizando procedimentos padronizados. Os resultados indicaram que a densidade de M. lateriflorum foi de 840 kg/m3 o que a caracteriza como uma madeira de alta densidade. O estudo revelou novamente uma forte correlação (83-99%) entre as densidades das madeiras e as características de resistência mecânica. Além disso, a retração tangencial e radial da madeira verde até 12% de umidade foi de 9,46% e 6,57%, respectivamente. A retração longitudinal foi de 0,65%. Os valores médios de resistência registrados em N/mm2 com 12% de umidade foram: módulo de elasticidade (19.724), módulo de ruptura (143), compressão (62,4), cisalhamento (20,5) e tração paralela às fibras (149,2). O ensaio de dureza Janka registrou valores médios de 15,7 e 14,3 kN nas direções radial e tangencial. Assim, M. lateriflorum poderia ter seu uso promovido como uma escolha eficiente para construção e aplicações estruturais.Palavras-chave: valorização da madeira; propriedades físico-mecânicas; qualidade da madeira.